Palynology of the stingless bees, Heterotrigona itama (Hymenoptera: Apidae) in the coastal forest of Terengganu - Roziah Ghazi,; Abd Jamil Zakaria,; Wahizatul Afzan Azmi,; Fahimee Jaapar,; Norhayati Ngah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Stingless bee, Heterotrigona itama (Apidae, Meliponini) is one of the few social bee species naturally occurring in the coastal forests of Terengganu, where a wide variety of flowering plants are available throughout the year. Studies on the botanical sources of honey and bee bread produced by stingless bees in Malaysia are well-documented. However, data pollen load of stingless bees varies based its species-specific characteristics, behavioral factors and various environmental condition at certain location are lacking. Therefore, palynological investigation is important to explore the floral collection of H. itama, especially in the coastal forests. Six colonies of H. itama were selected for sampling pollen grains in the Taman Rimba Ilmu Tanah Beris (TRIBE), located at Universiti Sultan Zainal Abidin, Besut Campus, Terengganu, Malaysia. Pollen grains were collected from the pollen baskets of H. itama foragers. The data was analyzed based on the following categories: dominant pollen (>45%), accessory pollen (15-45%), isolated pollen (3-15%), and occasional pollen (<3%). Two-way Cluster Analysis on grouped pollen types was done to classify their similarity by hive and month, while Detrended Correspondence Analysis (DCA) to illustrate pollen assemblage ordination across different months and hives was done. Overall, 43 plant species belonging to 20 families were visited by H. itama, as observed directly and through palynological analysis. However, only 21 plant species from 20 families were successfully identified. The most abundant families collected by H. itama were Fabaceae (Acacia spp.) and Lamiaceae (Orthosiphon aristatus), followed by Passifloraceae (Passiflora edulis) and Asteraceae (Bidens pilosa and Cosmos caudatus). Other types of pollen grains were considered as accessory, isolated, or occasional pollen grains. Highest amounts of pollen types were collected in May 2016, as it was the flowering season for most plant species in the TRIBE. The findings of this study can help us develop more effective strategies for the conservation of coastal forest ecosystems, and ensuring the sustainability of stingless bee habitats that are crucial for plant pollination.